Biosorption Of Lead (Ii) Ions By Stem Of Manihot Esculenta (Cassava Stem) - Selvam, Sathiswaran (Universiti Sains Malaysia, 2017)
Heavy metals becoming pollutants due to its non-biodegradable characteristics, toxicity and persistence in the environment where lead is one of it. In this study, Manihot esculenta stem biomass was used in the biosorption process of lead (II) ions in batch. The effects of pretreatment (raw, acid and alkali), pH control (2-6), biomass loading (0.25 g – 1.25 g), contact time (20 minutes – 100 minutes) and initial metal concentration (50 mg/L – 250mg/L) were studied on the removal of lead (II) ions from aqueous solution. Observations stated that the suitable conditions for high biosorption capacity, which is removal up to 99.60% by M. esculenta stem are alkali pretreated biosorbent, at pH 6, biomass loading of 0.75 g, metal concentration of 100 mg/L, in 60 minutes contact time. It is also found that Langmuir isotherm model (R2= 0.9783) fits well for this biosorption process as adsorption isotherm, rather than Freundlich isotherm model (R2= 0.7581). Kinetic data modelling resulted in good fit with the pseudo-second-order model (R2= 1.000) compared to pseudo-first-order model (R2= 0.6244). Overall result shows that M. esculenta stem is a good biosorbent, and can be used as an alternative low-cost biosorbent for removal of lead (II) ions.